Peningkatan Hasil Belajar Ekonomi dengan Menggunakan Media Pembelajaran Audiovisual pada Peserta Didik Kelas XI IPS 3 SMA Negeri 2 Palangkaraya Tahun Pelajaran 2016/2017 - Yayuk Sri Rahayu; Miftahurrizqi Miftahurrizqi (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2019)
The importance of this study aims to: (1) Improve economic learning activities after using audio-visual media for students of class XI IPS 3 of SMAN 2 Palangka Raya, (2) Improve financial learning outcomes using audio-visual media of XI IPS 3 students at SMAN 2 Palangka Raya. The research method used in this study is classroom action research (CAR). The subjects in the study were class XI IPS 3 totalling 35 students consisting of 20 men and 15 women. There are two data collection techniques, namely pre-test and post-test. The results of this study indicate that: (1) Activity of students during the learning process by using audiovisual media in the form of economic learning videos becomes more active. This is shown in the first cycle obtaining a score of 3.36 with a good category, and in the second cycle experiencing an increase to 3.8 with a good group, (2) The learning outcomes of students of class XI IPS 3 at SMAN 2 Palangka Raya using audiovisual media experienced the increase from the preliminary data on the pre-action average is 67.5, and the completeness in the classical is 41.17%. The average value in the first cycle is 80.30 and completeness in classical is 70%. The average cost in the second cycle is 91, and the integrity is in the traditional 100%.